Popular music education: A white paper by the Association for Popular Music Education. Issue 3 (1st December 2018) - Smith, Gareth Dylan; Powell, Bryan; Fish, David Lee; Kornfeld, Irwin; Reinhert, Kat
In this white paper, board members of the Association for Popular Music Education set out practices, approaches and domains that account for popular music education as understood in the present moment in largely English-speaking contexts. Popular music education has come of age as a field, overlapping with fields including popular music studies, music education, music business, music technology and music production, community music, media studies, ethnomusicology and communication studies. Popular music education is diverse and inclusive. It also has deep commercial and industrial connections. It includes school teaching, music teacher education and Higher music education. Popular music education scholarship and practice are expanding. The authors invite responses to this white paper in order to engender discussion and curate a community of practitioners and scholars.